Novel Findings from New Estimation between Green Monetary Policy and Environmental Sustainability in Europe: Does Institutional Quality Matter? - Nguyet, Pham Thi Anh (International Journal of Energy Economics and Policy, 2025)
We expand the previous study on the link between green monetary policy index (GMP) and environmental sustainability (ES) by empirically examining the moderating role of institutional quality. Various econometric approaches were employed in the data set of 17 European Union (EU) member nations from 2001 to 2022. As in previous studies, our estimation results demonstrate that promoting green monetary policies can increase overall environmental performance (EPI). Additionally, promoting specific policies such as GMP_Credit_Operations, GMP_Foreign_Asset_Purchases, and GMP_Domestic_Asset_Purchases can also increase one of the three environmental performance aspects. To further discuss the role of GMP, we reveal the impacts of green monetary policies on three dimensions of ES over different time horizons. The results show that GMP has a positive impact, making ES more likely to persist in the long term. Finally, we analyze the interaction between variables representing institutional quality and the impact of GMP on ES. According to our results, nations with well-developed institutional structures may have a greater favourable impact on green monetary strategies.